Implementation of Islamic Counseling Spiritual Perspective in Class II-B Corrective Institution Lubuk Pakam North Sumatera - Lubis, Hasan Hamzah; Fakhrurrozi, Fakhrurrozi (MODELING: Jurnal Program Studi PGMI, 2024)
This study discusses the Implementation of Islamic Counseling Perspective Spirituality in Class IIB Lubuk Pakam Penitentiary. This study uses qualitative research methodology. The results of this study are that the Implementation of Islamic Counseling Perspective Spirituality is 1) making a plan by determining the time, material, and material, and 2) the implementation is by implementing what has been planned, for example with the title "The Importance of Learning Tauhid" namely the reasons why learning tauhid are; a) Because Allah created us to believe in Him, b) The requirement to enter heaven must be to believe in tauhid, c) Tauhid is the reason for the elimination of sins (mistakes), d) Tauhid is the reason for the arrival of tranquility, e) Good deeds are not accepted until someone believes in tauhid, f) Tauhid is the reason for the multiplication of goodness or multiplication of rewards, g) Tauhid is the reason for guidance and a sense of security, and h) Tauhid is the reason for getting the intercession of the Prophet sallallaahu 'alaihi wa sallam.